CT variants of the caudal vena cava in 121 small breed dogs. Issue 6 (11th September 2019) - Ryu, Chanyoung; Choi, Sooyoung; Choi, Hojung; Lee, Youngwon; Lee, Kija
Abstract: Computed tomography is increasingly used as a treatment planning method in canine patients with diseases of the retroperitoneum, however, published information on normal variations in the caudal vena cava (CVC) are currently lacking. The objectives of this retrospective descriptive study were to characterize CVC variants using CT angiography in a sample of small breed dogs and localize the CVC bifurcations for each variant. Inclusion criteria were small breed dogs (weight ≤ 15) that underwent contrast‐enhanced CT scans of the CVC, abdominal aorta, and CVC tributaries. A total of 121 small breed dogs were sampled. Four right‐sided and one left‐sided CVC variations were identified: normal (88/121, 72.7%), caudal‐partial split (17/121, 14.0%), partial duplication (8/121, 6.6%), complete duplication (7/121, 5.8%), and left‐sidedness (1/121, 0.8%). The mean lumbar vertebral levels of the CVC bifurcation were L6.39 ± 0.41, L5.70 ± 0.35, L4.39 ± 0.42, L2.74 ± 0.38, and L6.4 in the normal, caudal‐partial split, partial duplication, complete duplication, and left‐sidedness types, respectively. The location of the CVC bifurcation, the relationship between the aortic trifurcation and the CVC bifurcation, and the location of the bilateral deep circumflex iliac veins with respect to the CVC bifurcation were significantly different among the right‐sided types ( P ≤ .001). Bilateral deep circumflex iliac veins joined to the ipsilateral common iliac veins and the CVC in the caudal‐partial split and duplication types, respectively. The results of this study indicated that canine CVC variants may be frequent and should be considered during surgery or diagnostic imaging of the retroperitoneum.